DATA PENYAKIT NEWCASTLE DISEASE (ND) DI BALAI BESAR VETERINER (BB VET) WATES YOGYAKARTA TAHUN 2012-2013 - , ZIPORA PRILI A, Prof. drh. Bambang Hariono, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The apprenticeship program I have conducted to observe kinds of animal disease and its disseminated disease in Yogyakarta, Central Java, and East Java. This apprenticeship program also I have conducted to observe identification methods of Newcastle disease (ND) virus by using hemaglutination assay (HA) and hemaglutination inhibition (HI) test at Balai Besar Veteriner (BB Vet) Wates Yogyakarta. The material used was disease data of Newcastle disease in 2012-2013 and identification method of Newcastle disease at Balai Besar Veteriner (BB Vet) Wates Yogyakarta on April, 1st-4th 2014. The collecting data was conducted by following daily activities in the laboratory, observing, and interview with the staffs at Balai Besar Veteriner (BB Vet) Wates Yogyakarta. In 2012, there were 35 cases of Newcastle disease from 204 samples (17,16%). In 2013, there were 234 cases from 551 samples (42,47%). Based on the data, Balai Besar Veteriner (BB Vet) Wates Yogyakarta, detected antigen ND by testing hemagglutination assay (HA). It purposed to observe the virus that can coagulate chicken erythrocyte and testing hemagglutination inhibition assay (HI) to observe ND virus.